Household food insecurity is negatively associated with achievement of prenatal intentions to feed only breast milk in the first six months postpartum - Francis, Jane; Mildon, Alison; Tarasuk, Valerie; Frank, Lesley (Frontiers in Nutrition, 2024)
Background: Household food insecurity (HFI) has been associated with suboptimal breastfeeding practices. Postpartum factors reported by caregivers include stressful life circumstances and maternal diet quality concerns. It is unknown whether prenatal breast milk feeding intentions, a well-established predictor of breastfeeding outcomes, differ by HFI status. We explored associations between HFI and prenatal intentions to feed any and only breast milk in the first 6 months postpartum, and achievement of these intentions. Methods: We utilized data from self-identified biological mothers with children 6-12 months of age who responded to a retrospective, cross-sectional online infant feeding survey conducted in Nova Scotia, Canada. HFI (yes/no) was assessed using the Household Food Security Survey Module. Prenatal intentions to feed any and only breast milk were assessed based on responses to five options for infant milk feeding plans. Achievement of intentions was assessed by breast milk and formula feeding practices in the first 6 months. Multivariable logistic regressions were conducted, adjusting for maternal socio-demographics. Results: Among 459 respondents, 28% reported HFI; 88% intended to feed any breast milk and 77% intended to feed only breast milk, with no difference by HFI status. Of those intending to feed any breast milk, 99% succeeded, precluding further analysis. Among mothers who intended to provide only breast milk, only 51% achieved their intention, with lower odds among those with HFI (aOR 0.54, 95% CI 0.29-0.98). Conclusion: HFI was not associated with intentions for feeding breast milk in the first 6 months postpartum, but mothers with HFI were less likely to achieve their intention to provide only breast milk. Further research is needed to understand the underlying reasons for this and to guide intervention designs to address HFI and help mothers reach their breastfeeding goals.